The burden of atherosclerotic cardiovascular disease among working-age people across SDI regions: an age–period–cohort study based on the GBD 2021 - Yan, Yuan; Xie, Jing; Wu, Hui; Tang, Yong-Gang; Yin, Yang-Guang (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAtherosclerotic cardiovascular disease (ASCVD) remains a leading health threat to the working-age population globally, with marked disparities in incidence and mortality across countries at different levels of socio-demographic development.MethodsBased on data from the Global Burden of Disease Study 2021, we used an age-period-cohort (APC) model to evaluate trends in the incidence and mortality of three major ASCVD subtypes—ischemic heart disease (IHD), ischemic stroke (IS), and peripheral artery disease (PAD)—among working-age adults (15–64 years) from 1992 to 2021 across five socio-demographic index (SDI) regions. The model further explored the contributions of age, period, and cohort effects.ResultsAlthough age-standardized incidence and mortality rates of ASCVD have declined in most high-SDI regions and globally, the absolute number of cases and deaths has continued to rise, especially in middle- and low-SDI regions. Notably, PAD showed increasing incidence trends in several developing regions, suggesting persistent gaps in public awareness and preventive efforts.ConclusionASCVD remains a significant global public health challenge among the working-age population. SDI-specific and accessible interventions, along with strengthened cross-sector collaboration, are urgently needed to promote effective prevention and control of ASCVD worldwide.